Prevention of abdominal wound infection (PROUD trial, DRKS00000390): study protocol for a randomized controlled trial - Heger, Ulrike; Voß, Sabine; Knebel, Phillip; Dörr-Harim, Colette; Neudecker, Jens; Schuhmacher, Christoph; Faist, Eugen; Diener, Markus K.; Kieser, Meinhard; Seiler, Christoph; Büchler, Markus W. (Trials, 2011)
Wound infection affects a considerable portion of patients after abdominal operations, increasing health care costs and postoperative morbidity and affecting quality of life. Antibacterial coating has been suggested as an effective measure to decrease postoperative wound infections after laparotomies. The INLINE metaanalysis has recently shown the superiority of a slowly absorbable continuous suture for abdominal closure; with PDS plus® such a suture has now been made available with triclosan antibacterial coating.
Gesehen am 28.09.2022